The Test on the Relationship Between Economic Growth and Iran's Financial Structure - Seyyed Ahmad Mir Motahari (Faslnāmah-i Pizhūhish/Nāmah-i Iqtisādī, 2007)
In this paper we address the issue of whether financial structure influences economic growth. Three competing views of financial structure exist in the literature: the bank base, the market base and the financial services view. Recent empirical studies examine their relevance by utilizing panel and cross- section approaches. This paper utilizes time series data of Iran .We find significant effects of financial structure on real per capita output, which is in contrast to some of the recent findings.